2010
DOI: 10.1007/s00276-010-0684-7
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic kidney with varied vasculature: demonstrated by CT angiography

Abstract: An ectopic kidney was found incidentally in a 20-year-old male patient during the abdominopelvic CT angiography. It was situated on the right side at the abdominopelvic junction, partly in the abdomen at the level of the intervertebral disc between L3 and L4 superiorly and partly in the greater pelvis at the level of the promontorium and close to the inferior border of the sacroiliac joints. It was supplied by two arteries which were nearly in the same caliber, and each of which branched from the common iliac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…In our study, we found renal malrotation in both the right and left kidneys of six patients (n = 6/3000, 0.2%). The kidneys, sometimes outside the normal anatomic position (ectopic kidneys), can be located in the pelvic, abdominal, or thoracic regions, or on the contralateral side (13)(14)(15), and are more frequently found on the left side than on the right side (16). Ectopic kidneys have a reported frequency of 0.2% to 0.9%.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found renal malrotation in both the right and left kidneys of six patients (n = 6/3000, 0.2%). The kidneys, sometimes outside the normal anatomic position (ectopic kidneys), can be located in the pelvic, abdominal, or thoracic regions, or on the contralateral side (13)(14)(15), and are more frequently found on the left side than on the right side (16). Ectopic kidneys have a reported frequency of 0.2% to 0.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Since anomalous venous structures tend to be dilated and tortuous, causing injury more easily, lack of preoperative recognition of renal vein anomalies can have potentially disastrous consequences (6). Intraoperative trauma of an anomalous vein may cause life-threatening hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular variations associated with an ectopic kidney can predispose to iatrogenic trauma during interventional procedures and emergency operations (Kara et al 2011). Giant hydronephrosis in an ectopic kidney is an extremely rare disorder that can present as an asymptomatic abdominal mass (Hsieh et al 2013).…”
Section: Complications Of Pelvic Kidneymentioning
confidence: 99%
“…A pelvic kidney creates potential difficulties in the management of patients requiring aortic surgery (Krahn and Taylor 1993). The renal pelvis is usually anterior to the parenchyma, and surgical operation for acute appendicitis could create complications (Kara et al 2011). Ectopic kidneys can be associated with autosomal dominant polycystic kidney disease (ADPKD) and a pelvic kidney has been associated with a reverse sigmoid colon (Chen et al 2010).…”
Section: Complications Of Pelvic Kidneymentioning
confidence: 99%